Potential Of Selected Antagonistic Bacteria In Controlling Damping-Off Disease Of Brassica Chinensis L. Caused By Pythium Myriotylum Drech - Zahara, Hafni (2004)

(untitled)
The causal agent of damping-off of Brassica chinensis was isolated and identified as Pythium myriotylum Drech. based on its morphological characteristics. Isolation of bacteria from the rhizosphere region of B. chinensis seedlings resulted in the isolation of 118 bacterial isolates where 6 isolates were found to have antagonistic activities against P. myriotylum.Using the Biolog® Identification System, these antagonistic bacteria were identified as Serratia marcescens, Rhodococcus erythropolis, Tsukamurella inchonensis, Burkholderia cepacia (Syn. Pseudomonas cepacia), Pseudomonas aeruginosa 1 and Pseudomonas aeruginosa 2. Based on dual culture test, B. cepacia was the best antagonist in inhibiting the mycelial growth of P. myriotylum.. B. cepacia inhibited the mycelial growth of P.myriotylum (24.50 mm) based on dual culture and clearing zone inhibition of 80.00 mm, based on colony degradation tests. In double media overlay tests, B. cepacia, P. aeruginosa 1 and P. aeruginosa 2 were antagonistic with no radial mycelial growth of P. myriotylum. Experiments in the screenhouse indicated that B. cepacia was more effective in protecting the B. chinensis seeds against P. myriotylum than P. aeruginosa 1 and P. aeruginosa 2, and was equally effective as fungicide Captan®. Soil treatment was more effective than seed treatment in increasing the percentage seedling emergence, percentage survival plants and dry weight (g) of B. chinensis.